INDIVIDUAL PERCEPTIONS OF PUBLIC SECTOR’S RISK CULTURE - Christiani, Maria Riche; Adhariani, Desi (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2025)
Effective risk management in the public sector is essential; however, individual perspectives reveal gaps in implementation and a weak risk culture, which increase the potential for errors, fraud, and corruption. This study evaluates individual perceptions that shape organizational culture to support effective risk management at Office B, a public service agency managing a significant budget. A qualitative case study approach was employed using method and data triangulation (document analysis, surveys, and interviews), based on frameworks from the Institute of Risk Management and Schein’s Organizational Culture Theory. The findings indicate that the risk culture is "partially fulfilled", with most individuals classified as composed, moderately risk-aware but passive and compliance-oriented. Risk-based decision-making is reactive, and risk communication remains limited due to fear of consequences. The underlying culture emphasizes formality, compliance, and caution. Office B must strengthen its risk culture through leadership, transparency, and structured training.